Rotigotine protects against oxidized low-density lipoprotein(ox-LDL)-induced damages in human umbilical vein endothelial cells(HUVECs). Issue 2 (20th December 2021) - Kang, Hui; Yu, Hui; Fan, Jingxiu; Cao, Ge
ABSTRACT: Rotigotine is a non-ergoline dopamine agonist that has been licensed for the treatment of Parkinson's disease. Cardiovascular diseases are the world's leading cause of death. Ox-LDL- induced endothelial damages are involved in the initiation and progression of cardiovascular diseases. In this study, we assessed the beneficial properties of Rotigotine on ox-LDL-induced insults to HUVECs to highlight its potential use in the treatment of cardiovascular diseases. Our findings show that Rotigotine suppresses the expressions of low-density lipoprotein receptor (LDL-R), proprotein convertase subtilisin/kexin type 9 (PCSK-9), and sterol regulatory element-binding protein (SREBP-2). It also inhibits ox-LDL-induced cholesterol accumulation in endothelial cells (ECs), improves U937 monocytes adhesion, and decreases the representation of NADPH oxidase (NOX-4) and generation of reactive oxygen species (ROS) in endothelial cells (ECs). Furthermore, Rotigotine inhibited the expressions of both vascular cellular adhesion molecule-1 (VCAM-1) and intercellular adhesion molecule-1 (ICAM-1) in HUVECs and had anti-inflammatory efficacy in ox-LDL-induced cells by inhibiting the expressions of pro-inflammatory cytokines. Notably, Rotigotine inhibits the activation of nuclear factor-kappaB (NF-κB) by preventing nuclear translocation of NF-κB p65 and reducing the luciferase activity of NF-κB reporter. We, therefore, conclude that these effects of Rotigotine on HUVECs suggest that it may play a therapeutic role in cardiovascular diseases.